BRAND IMAGE AS A DETERMINANT OF EIGER PRODUCT REPURCHASE THROUGH BRAND TRUST - Armadani, Erika Suci; Utari, Woro (STIE Pelita Nusantara Semarang, 2025)
This research aims to examine the significant effects of Price, Brand Image, and Product Quality on Repurchase Intention with Brand Trust as an intervening variable for Eiger products in Surabaya City. The sampling technique used was purposive sampling, resulting in a sample size of 75 consumers of Eiger products in Surabaya. This research is explanatory research with a quantitative approach. Data collection was conducted through online questionnaires distributed via Google Forms. Data analysis was performed using Partial Least Square. The results show that the direct effects are as follows: price has a positive and significant effect on brand trust; price has a positive and significant effect on repurchase intention; brand image has a positive and significant effect on brand trust; brand image has a positive and significant effect on repurchase intention; product quality has a positive and significant effect on brand trust; product quality has a positive and significant effect on repurchase intention; and brand trust has a positive and significant effect on repurchase intention. Additionally, the indirect effects indicate that price, brand image, and product quality positively and significantly influence repurchase intention through brand trust.